White anti-static particle and preparation method thereof
By growing ITO particles in situ on the powder surface in the thermally controlled coating, white anti-static particles were prepared, which solved the problem that coatings on high-orbit spacecraft were difficult to achieve anti-static functions, while maintaining the heat dissipation performance of the coating.
Patent Information
- Application Number
- CN202411735101.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing thermally controlled coatings are difficult to achieve anti-static functions on high-orbit spacecraft. At the same time, the addition of conductive agents will increase the solar absorption ratio and reduce heat dissipation capabilities.
By growing ITO particles in situ on the surface of powders such as ZnO, TiO2, MgO or BaSO4, white antistatic particles were prepared, and the growth of ITO particles was regulated by heterogeneous precipitation method to ensure that they were evenly distributed on the surface of the powder.
The preparation of white anti-static particles is realized, and it has good anti-static properties, while not affecting the solar absorption ratio of the coating, and maintaining the heat dissipation performance of the coating.
Smart Images

Figure CN119552533A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of material preparation, and relates to white antistatic particles and a preparation method thereof, and specifically relates to white antistatic particles used for coatings and a preparation method thereof, and especially relates to white antistatic particles used for thermal control coatings of spacecraft and a preparation method thereof. Background Art
[0002] Thermal control coatings are usually applied to the surface of spacecraft. They are special functional materials essential for the thermal control system of spacecraft and are crucial to controlling the surface temperature of spacecraft and its individual units. Thermal control coatings adjust the solar absorption ratio (α S ) and infrared radiation rate (ε H ) Two key optical and thermal performance parameters, namely thermal radiation performance, control the spacecraft surface to absorb heat energy from space (sun, earth, planets, etc.) and the spacecraft to radiate heat energy to space, and control the ratio of the two within a certain range, so that the structural components and equipment of the spacecraft are within the required operating temperature range. At the same time, thermal control coatings are also often used inside spacecraft to enhance the heat exchange between the internal cabin wall and the single machine surface, and to make the temperature inside the spacecraft evenly distributed through radiation heat exchange.
[0003] Due to the impact of charged particles on high-orbit spacecraft (such as geosynchronous orbit), the surface potential accumulation can reach thousands of volts, which will seriously affect the normal operation of electronic equipment after discharge. Therefore, the thermal control coating used for high-orbit spacecraft must have anti-static properties. The resistance of the currently commonly used ZnO powder exceeds 10 5 KΩ-cm, the surface resistance of the coating prepared by it far exceeds the anti-static requirement of 10 12 Ω / □, does not have antistatic function. The method of adding conductive additives such as aluminum powder, ITO powder, ATO powder, etc. to the thermal control coating can reduce the surface resistance of the ZnO coating, but the conductive agent itself is usually gray, light green, etc., which will increase the solar absorption ratio of the coating and thus reduce the heat dissipation capacity of the coating. Therefore, it is urgent to develop an antistatic particle that has both antistatic function and does not reduce the heat dissipation capacity of the coating. Summary of the invention
[0004] In view of the above problems, the present invention provides white antistatic particles and a preparation method thereof.
[0005] In a first aspect, the present invention provides a white antistatic particle, comprising: a powder, and ITO particles grown in situ on the surface of the powder; the powder is at least one of ZnO powder, TiO2 powder, MgO powder, and BaSO4 powder; the ITO particles are composed of In and Sn; Preferably, the particle size of the powder is 100-500 nm; the particle size of the ITO particles is 5-20 nm.
[0006] Preferably, based on the total mass of the white antistatic particles being 100%, the mass ratio of the powder is 75-99%, and the mass ratio of the ITO particles is 1-25%.
[0007] Preferably, the molar ratio of In to Sn in the ITO particles is (6-9):1.
[0008] Preferably, the volume resistance of the white antistatic particles is ≤2000KΩ-cm.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned white antistatic particles, comprising: (1) dissolving the powder in deionized water, stirring in a water bath at a constant temperature, to obtain a dilute suspension of the powder; the dilute suspension has a solid content of 5 to 20%; (2) weighing crystalline tin chloride (SnCl4·5H2O) and indium chloride tetrahydrate (InCl3·4H2O) according to a stoichiometric ratio and dissolving them in deionized water to obtain an ITO precursor solution; the concentration of the ITO precursor solution is 0.01 to 0.5 mol / L; (3) adding the obtained ITO precursor solution dropwise to the dilute suspension of the powder, adjusting the pH value of the solution to 8 to 12 for reaction, and after the reaction is completed, filtering, washing, and drying the product to obtain a composite powder containing ITO; (4) calcining the obtained ITO-containing composite powder to obtain the white antistatic particles.
[0010] Preferably, in step (1), the temperature of the water bath constant temperature stirring is 30 to 80°C.
[0011] Preferably, in step (2), the stoichiometric ratio of the crystalline tin chloride to indium chloride tetrahydrate is 1:(4-10).
[0012] Preferably, in step (3), aqueous ammonia is added to the system to adjust the pH value, and the mass fraction of the aqueous ammonia is 25 to 28%.
[0013] Preferably, in step (3), the mass ratio of ITO contained in the ITO precursor solution to the mass ratio of the powder in the dilute suspension is 1:99 to 25:75.
[0014] Preferably, in step (3), the obtained ITO precursor solution is added dropwise to a dilute suspension of the powder for reaction, and the mixture is heated and stirred at 30 to 90° C. for 1 to 12 hours; the pH value is adjusted to 8 to 12, and the mixture is heated and stirred at 30 to 90° C. for 1 to 12 hours.
[0015] Preferably, in step (3), the washing solvent is deionized water or anhydrous ethanol.
[0016] Preferably, in step (4), the calcination temperature is 300-700° C. and the calcination time is 4-24 hours.
[0017] Beneficial effects: (1) The white antistatic particles prepared by the present invention are white and have good antistatic properties, and can be used in the fields of automobiles, ships, aviation, aerospace, etc. (2) The method for preparing white antistatic particles provided by the present invention is simple to operate, low in cost, short in time, and easy to promote and apply in industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a SEM image of the white antistatic particles prepared in Example 1; Figure 2 The solar reflection spectra of the white antistatic particles prepared in Example 1 and Example 2 and the solar reflection spectra of the ZnO particles; wherein S-1 represents Example 1; S-2 represents Example 2. DETAILED DESCRIPTION
[0019] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.
[0020] In the present invention, the heterogeneous precipitation method is used to adjust the mass ratio of the ITO precursor to the powder suspension to avoid the self-nucleation growth caused by the excessive concentration of the ITO precursor, and the ITO particles are grown in situ on the powder surface in the dilute suspension (from Figure 1 It can be seen that the ITO particles grow in situ on the powder surface, rather than generating ITO powder particles separately). In addition, since the proportion of ITO particles in the antistatic particles in the present invention is relatively low, the antistatic particles present the color of the powder, that is, the present invention prepares white antistatic particles. Therefore, the preparation method of the present invention can grow ITO particles in situ on the powder surface, and realize the preparation of white antistatic particles, thereby not affecting the solar absorption ratio of the coating, and further not affecting the heat dissipation performance of the coating.
[0021] The following is an exemplary description of the preparation method of the white antistatic particles provided by the present invention.
[0022] The powder is dissolved in deionized water and stirred in a water bath to obtain a dilute suspension of the powder.
[0023] In an optional embodiment, the temperature of the water bath thermostatic stirring is 30-80°C, for example 50°C.
[0024] In an optional embodiment, the dilute suspension of the powder has a solid content of 5 to 20%.
[0025] Crystalline tin chloride (SnCl4·5H2O) and indium chloride tetrahydrate (InCl3·4H2O) were weighed in a stoichiometric ratio and dissolved in deionized water to obtain an ITO precursor solution.
[0026] In an optional embodiment, the stoichiometric ratio of the crystalline tin chloride to indium chloride tetrahydrate is 1:(4-10); preferably 1:9 or 2:8; more preferably, in order to improve the antistatic performance of the ITO particles, the molar ratio of In to Sn is 1:9.
[0027] The obtained ITO precursor solution is added drop by drop to the dilute suspension of the powder for reaction, heated and stirred at 30-90°C for 1-12 hours, and then ammonia water (NH3·H2O) is added drop by drop to the system to adjust the pH value of the solution to 8-14, so that the ITO precursor can smoothly generate ITO particles, and continue to heat and stir at 30-90°C for 1-12 hours. After the reaction is completed, the product is filtered, and the product is washed with a large amount of deionized water and anhydrous ethanol until there is no chloride ion in the filtrate, and then placed in an oven for drying to obtain a composite powder containing ITO. If the pH is <8, ITO cannot be smoothly precipitated in a heterogeneous phase, that is, ITO particles cannot be prepared from the precursor.
[0028] In an optional embodiment, the mass ratio of the ITO mass contained in the ITO precursor solution to the mass ratio of the powder in the dilute suspension is 1:99 to 25:75. If the mass ratio of the ITO mass contained in the ITO precursor solution to the powder in the dilute suspension is too large (or the mass of the ITO contained in the ITO precursor solution is too high), the ITO powder will nucleate and precipitate alone, and cannot be heterogeneously precipitated on the ZnO surface to form ITO particles. Although the volume resistivity of the powder is low, the solar absorption ratio increases and the heat dissipation performance decreases.
[0029] In an optional embodiment, the mass fraction of the ammonia water is 25-28%. Preferably, the pH value of the solution is adjusted to 10-11.
[0030] The obtained ITO-coated composite powder is calcined and then cooled to room temperature to obtain the white antistatic particles.
[0031] In an optional embodiment, the calcination temperature is 300-700°C, for example, 500°C; the calcination time is 4-24h, for example, 12h. If the calcination time is too short or the calcination temperature is too low, ITO sintering is incomplete, ITO particles are not fully prepared, and the volume resistance of the powder increases.
[0032] In the present invention, each step is carried out under normal pressure.
[0033] In the present invention, the volume resistance of the white antistatic particles is tested by a powder resistance test method.
[0034] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0035] Example 1 (1) Weigh 100 g ZnO powder, dissolve it in 2000 ml deionized water, and stir it continuously in a constant temperature water bath at 50°C to prepare a dilute suspension of the powder; (2) Based on the weight of ITO powder of 5 g and the stoichiometric ratio of Sn:In in ITO of 1:9, the corresponding crystalline tin chloride (SnCl4·5H2O) and indium chloride tetrahydrate (InCl3·4H2O) were weighed and dissolved in deionized water to prepare an ITO precursor solution; (3) Add the ITO precursor solution drop by drop into the powder suspension, heat and stir at 50°C for 2 hours, then add ammonia water (NH3·H2O) drop by drop into the system, adjust the pH value of the solution to pH 8, and continue to stir and react at 50°C for 2 hours. After the reaction is completed, filter the product, wash the product with a large amount of deionized water and anhydrous ethanol until there is no chloride ion in the filtrate, and put it into an oven for drying; (4) The dried composite powder material is placed in a high-temperature furnace for calcination, the temperature is raised to 300° C. and kept at this temperature for 12 h, and then naturally cooled to room temperature to obtain white antistatic particles.
[0036] Example 2
[0037] The preparation process of the white antistatic particles in Example 2 is based on that in Example 1, with the only difference being that in step (1), the powder is BaSO4.
[0038] Example 3
[0039] The preparation process of the white antistatic particles in this embodiment 3 refers to that in embodiment 1, with the only difference being that in step (1), the powder is TiO2.
[0040] Example 4
[0041] The preparation process of the white antistatic particles in Example 4 is similar to that in Example 1, with the only difference being that in step (1), the powder is MgO.
[0042] Example 5
[0043] The preparation process of the white antistatic particles in Example 5 is similar to that in Example 1, with the only difference being that in step (2), the mass of the ITO powder is 10 g.
[0044] Example 6
[0045] The preparation process of the white antistatic particles in Example 6 is similar to that in Example 1, with the only difference being that in step (3), the pH value of the solution is adjusted to 10.
[0046] Example 7
[0047] The preparation process of the white antistatic particles in Example 7 is similar to that in Example 1, with the only difference being that in step (4), the calcination temperature is 500°C.
[0048] Comparative Example 1
[0049] In this comparative example 1, ZnO powder is directly used.
[0050] Comparative Example 2
[0051] The preparation process of the white antistatic particles in Comparative Example 2 is based on that in Example 1, with the only difference being that in step (3), the pH value of the solution is adjusted to 6.
[0052] Comparative Example 3
[0053] The preparation process of the white antistatic particles in Comparative Example 3 is similar to that in Example 1, except that in step (4), the calcination temperature is 200°C.
[0054] Comparative Example 4
[0055] The preparation process of the white antistatic particles in Comparative Example 4 is similar to that in Example 1, except that in step (2), the mass of the ITO powder is 30 g.
[0056] Table 1 lists the raw material composition, reaction conditions, volume resistance and solar absorption ratio of Examples 1-7 and Comparative Examples 1-4.
[0057] Table 1: Powder ITO powder pH temperature Volume resistance KΩ-cm Solar absorption ratio Example 1 ZnO 5g 8 300℃ 163.24 0.13 Example 2 <![CDATA[TiO2]]> 5g 8 300℃ 1031.51 0.13 Example 3 MgO 5g 8 300℃ 29.85 0.12 Example 4 <![CDATA[BaSO4]]> 5g 8 300℃ 222.97 0.13 Example 5 ZnO 10g 8 300℃ 568.06 0.12 Example 6 ZnO 5g 10 300℃ 38.61 0.13 Example 7 ZnO 5g 8 500℃ 7.04 0.12 Comparative Example 1 ZnO - - - 23754 0.12 Comparative Example 2 ZnO 5g 6 300℃ 18592 0.12 Comparative Example 3 ZnO 5g 8 200℃ 26915 0.13 Comparative Example 4 ZnO 30g 8 300℃ 49.28 0.26 .
[0058] It can be seen from Table 1 that the volume resistance of the white antistatic particles prepared by the present invention is significantly lower than the volume resistance of the ZnO powder in Comparative Example 1. Among them, it can be seen from Comparative Example 1 and Example 7 that increasing the sintering temperature will significantly reduce the volume resistance. Comparative Example 1 and Comparative Example 2 show that pH <8, and the powder resistance is relatively high. Comparative Example 1 and Comparative Example 3 show that the sintering temperature is too low and the powder resistance is relatively high. Comparative Example 1 and Comparative Example 4 show that the content of ITO powder is too high, and although the volume resistance is relatively low, the solar absorption ratio increases and the heat dissipation performance decreases.
[0059] Figure 1 This is a SEM image of the white antistatic particles prepared in Example 1. As can be seen from the image, the ITO particles are uniformly prepared on the powder.
[0060] Figure 2 The solar reflection spectrum of the white antistatic particles and the solar reflection spectrum of the ZnO particles prepared in Example 1. As can be seen from the figure, the solar reflection spectrum of the antistatic particles is basically consistent with the solar reflection spectrum of the ZnO particles, and does not affect the heat dissipation effect.
Claims
1. A white antistatic particle, characterized in that: include: Powder, and ITO particles grown in situ on the surface of the powder; The powder is at least one of ZnO powder, TiO2 powder, MgO powder and BaSO4 powder; the ITO particles are composed of In and Sn; Preferably, the particle size of the powder is 100 nm to 500 nm; and the particle size of the ITO particles is 5 to 20 nm.
2. The white antistatic particles according to claim 1, characterized in that: Taking the total mass of the white antistatic particles as 100%, the mass ratio of the powder is 75-99%, and the mass ratio of the ITO particles is 1-25%.
3. The white antistatic particles according to claim 1 or 2, characterized in that: The molar ratio of In to Sn in the ITO particles is (6-9):
1.
4. A method for preparing white antistatic particles according to any one of claims 1 to 3, characterized in that: include: (1) dissolving the powder in deionized water, stirring in a water bath at a constant temperature, to obtain a dilute suspension of the powder; the dilute suspension has a solid content of 5 to 20%; (2) weighing crystalline tin chloride and indium chloride tetrahydrate according to a stoichiometric ratio and dissolving them in deionized water to obtain an ITO precursor solution; the concentration of the ITO precursor solution is 0.01 to 0.5 mol / L; (3) adding the obtained ITO precursor solution dropwise to the dilute suspension of the powder, adjusting the pH value of the solution to 8 to 12 for reaction, and after the reaction is completed, filtering, washing, and drying the product to obtain a composite powder containing ITO; (4) calcining the obtained ITO-containing composite powder to obtain the white antistatic particles.
5. The preparation method according to claim 4, characterized in that: In step (1), the temperature of the water bath thermostatic stirring is 30 to 80°C.
6. The preparation method according to claim 4 or 5, characterized in that: In step (2), the stoichiometric ratio of the crystalline tin chloride to indium chloride tetrahydrate is 1:(4-10).
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (3), ammonia water is added to the system to adjust the pH value, and the mass fraction of the ammonia water is 25-28%.
8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (3), the mass ratio of ITO contained in the ITO precursor solution to the mass ratio of the powder in the dilute suspension is 1:99 to 25:
75.
9. The preparation method according to any one of claims 4 to 8, characterized in that: In step (3), the obtained ITO precursor solution is added dropwise to the dilute suspension of the powder for reaction, and the reaction is heated and stirred at 30-90° C. for 1-12 hours; the pH value is adjusted to 8-12, and the reaction is continued by heating and stirring at 30-90° C. for 1-12 hours.
10. The preparation method according to any one of claims 4 to 9, characterized in that: In step (4), the calcination temperature is 300 to 700° C. and the calcination time is 4 to 24 hours.
Citation Information
Patent Citations
Preparation method of TiO2 baseline-shaped conductive powder
CN106115776A
White conductive powder, conductive mixed powder, dispersion liquid, coating material, and membrane composition
WO2012091021A1